The Influence of Gender and Job Market Considerations on Accounting Students’ Career Choice as Public Accountants - Ridwan Fikri Maulana; Pupung Purnamasari (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The public accounting profession remains a highly prospective career path for accounting students. Nevertheless, interest in entering this field often diminishes over time, influenced by several factors, such as prevailing gender perceptions and challenging job market accessibility. This research seeks to examine and clarify the impact of gender and job market considerations on accounting students’ decisions to pursue careers as public accountants, focusing on accredited excellent universities in Bandung City. The study employs a quantitative approach with descriptive and verification methods. A nonprobability sampling technique, specifically purposive sampling, was used to select respondents. Data were gathered from 96 accounting students across 10 accredited excellent universities in Bandung City. Hypothesis testing was performed using the Partial Least Squares (PLS) method via the SmartPLS 4.0 application. The results indicate that both gender and job market considerations have a positive and significant influence on accounting students’ career decisions to become public accountants. These findings suggest that greater student awareness of gender dynamics in the workplace, combined with improved access to the public accounting job market, correlates with increased interest in choosing public accounting as a career.